Molecular sieve composite catalyst and its preparation method and application
By preparing the molecular sieve composite catalyst, the problem of active decay of existing catalysts in weak acid environments is solved, and the efficient curing and stable catalytic performance of polyurethane adhesives are achieved.
Patent Information
- Application Number
- CN202211520034.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-30
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2042-11-30
AI Technical Summary
The activity of existing organometallic catalysts is prone to attenuation or failure in systems containing trace amounts of water, weak acids, etc., resulting in the curing failure or the curing time of polyurethane adhesives.
A molecular sieve composite catalyst is used, which is used to prepare a molecular sieve composite catalyst by mixing the molecular sieve activation powder with alcohol compounds and then mixing it with a metal catalyst and a chelating agent. The catalyst forms a stable chelating state under a weakly acidic environment to avoid hydrolysis.
The attenuation rate of the catalyst is significantly reduced, the curing efficiency and stability of the polyurethane adhesive are improved, and the retention time of catalytic activity is extended.
Smart Images

Figure CN115746235B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalysts, and in particular to a molecular sieve composite catalyst and a preparation method and application thereof. Background Art
[0002] Polyurethane adhesives are widely used in the new energy automobile industry and the electronic and electrical industry. In order to promote the cross-linking and curing of the isocyanate-containing components and the active hydrogen-containing components such as hydroxyl, amino, and urea groups in the adhesive, a trace amount of organic metal catalysts is generally added. However, in systems containing trace amounts of water, weak acids, etc., the activity of the organic metal liquid catalyst is easily attenuated or ineffective, which directly leads to the curing failure of the adhesive. At the same time, in order to achieve a certain flame retardant level, a certain amount of weak acid flame retardant powder or flame retardant is usually added to the adhesive. The organic metal catalysts commonly used in the polyurethane industry will accelerate their failure in a weak acid environment, making the polyurethane adhesives added with general organic metal catalysts easy to cure and fail or the curing time is significantly extended.
[0003] Therefore, it is necessary to provide a novel molecular sieve composite catalyst and a preparation method and application thereof to solve the above-mentioned problems existing in the prior art. Summary of the invention
[0004] The object of the present invention is to provide a molecular sieve composite catalyst and a preparation method and application thereof. When the molecular sieve composite catalyst is added to a polyurethane adhesive, the catalyst has a low decay rate and can greatly improve the stability of the curing efficiency of the polyurethane adhesive.
[0005] To achieve the above object, the method for preparing the molecular sieve composite catalyst of the present invention comprises the following steps:
[0006] S1: mixing the molecular sieve activation powder and the alcohol compound and performing a dehydration reaction to obtain a first composite;
[0007] S2: mixing the first complex with a metal catalyst to react to obtain a molecular sieve supported catalyst;
[0008] S3: mixing the molecular sieve supported catalyst with a chelating agent to prepare a molecular sieve composite catalyst;
[0009] Wherein, the chelating agent is selected from one of benzoyl acetone, dipivaloyl methane, 2-hydroxyphosphonoacetic acid, hydroxyethylidene diphosphonic acid, tetramethyl heptanedione, heptafluorodimethyl octanedione, trifluorodimethyl hexanedione, hexafluoroacetylacetone, acetylacetone, and hydroxyethylethylenediaminetriacetic acid.
[0010] The beneficial effect of the preparation method of the molecular sieve composite catalyst of the present application is that: the preparation method of the present application uses a chelating six-membered ring chelating agent with strong chelating ability and the ability to form a high thermal stability with the catalyst metal ions or atoms to prepare the molecular sieve composite catalyst, which can make the prepared molecular sieve composite catalyst form a stable chelated state and will not hydrolyze even when distilled in a weakly acidic environment. The attenuation rate of the catalyst is greatly reduced when preparing the polyurethane adhesive, thereby improving the efficiency of preparing the polyurethane adhesive.
[0011] Preferably, the molecular sieve activation powder is selected from one or both of 3A molecular sieve activation powder and 4A molecular sieve activation powder, and the alcohol compound is selected from one of dipropylene glycol, diethylene glycol and glycerol.
[0012] Preferably, the step of mixing the molecular sieve activation powder and the alcohol compound and then subjecting them to a dehydration reaction to obtain the first composite comprises mixing the molecular sieve activation powder and the alcohol compound and subjecting them to a dehydration reaction for 1 hour at a temperature of 105 to 110° C. and a vacuum degree of -0.05 to -0.1 MPa to obtain the first composite.
[0013] Preferably, the temperature of the mixed reaction of the first complex and the organic metal catalyst is controlled to be 60-80°C.
[0014] Preferably, in the step of mixing the molecular sieve-supported catalyst with a chelating agent, the mass ratio of the molecular sieve-supported catalyst to the chelating agent is controlled to be 10:1 to 50:1.
[0015] Preferably, the organic metal catalyst is selected from the group consisting of dibutyltin bis(acetylacetonate), zirconium isooctanoate, dibutyltin dilaurate, dibutyltin diacetate, bismuth trioctanoate, stannous octanoate, dibutyltin dichloride, ferric acetylacetonate, aluminum acetylacetonate, bismuth isooctanoate, and zinc isooctanoate.
[0016] The present invention also provides a molecular sieve composite catalyst prepared by the preparation method, wherein the molecular sieve composite catalyst has a general structural formula (I):
[0017] M(CB) d [M(X) e ] f yBOHwL(I)
[0018] wherein M is one of tin, iron, zirconium, bismuth, aluminum, nickel, zinc or cobalt ions;
[0019] (CB) is a carboxylate ion, wherein the carboxylate ion is one of isooctanoate, laurate, acetylacetonate, cyclohexaneate, acetate, and propionate ions;
[0020] (X) is a chelating group, wherein the chelating group is one of β-diketone, enone, alkylphosphine, alcohol, phenol, crown ether, secondary amine, imine, azo or thiol;
[0021] B is an alkali metal ion, wherein the alkali metal ion is one of K and Na ions;
[0022] L is an organic chelating agent, which is one of benzoyl acetone, dipivaloyl methane, 2-hydroxyphosphonoacetic acid, hydroxyethylidene diphosphonic acid, tetramethyl heptanedione, heptafluorodimethyl octanedione, trifluorodimethyl hexanedione, hexafluoroacetylacetone, acetylacetone or hydroxyethylethylenediaminetriacetic acid;
[0023] d, e, and f are all integers greater than 0, and the values of d, e, and f make the composite catalyst electrically neutral;
[0024] y is greater than or equal to 0.1 and less than or equal to 5;
[0025] w is greater than or equal to 0.0001 and less than or equal to 5.
[0026] The beneficial effect of the molecular sieve composite catalyst of the present invention is that the molecular sieve composite catalyst can form a stable chelated state and does not hydrolyze during distillation in a weakly acidic environment. The attenuation rate of the catalyst is greatly reduced when preparing polyurethane adhesives, thereby improving the efficiency of preparing polyurethane adhesives.
[0027] The present invention also provides an application of a molecular sieve composite catalyst, comprising mixing a combination material A with a combination material B to prepare a polyurethane adhesive, wherein the combination material A comprises a polyol, a chain extender, a flame retardant, an auxiliary catalyst, a thermal conductive powder, a molecular sieve activation powder and a molecular sieve composite catalyst prepared by the above preparation method, and the combination material B comprises an isocyanate prepolymer, a flame retardant, a thermal conductive powder and a water scavenger.
[0028] The beneficial effect of the application of the molecular sieve composite catalyst of the present invention is that the molecular sieve composite catalyst can form a stable chelated state and does not hydrolyze during distillation in a weakly acidic environment. The attenuation rate of the catalyst is greatly reduced when preparing the polyurethane adhesive, thereby improving the efficiency of preparing the polyurethane adhesive.
[0029] Preferably, the mass parts of the components of the combination material A are: 100 parts of the polyol, 3-8 parts of the chain extender, 0.05-2 parts of the auxiliary catalyst, 20-60 parts of the thermal conductive powder, 5-15 parts of the molecular sieve activation powder and 0.05-2 parts of the molecular sieve composite catalyst.
[0030] Preferably, the weight parts of the components of the combination material B are: 100 parts of the isocyanate prepolymer, 10-30 parts of the flame retardant, 50-80 parts of the thermal conductive powder and 0.05-1 part of the dehydrating agent.
[0031] Preferably, the mass fraction of isocyanate groups in the isocyanate prepolymer is 8-20%. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 Schematic diagram of the catalytic mechanism of the base on the reaction of isocyanate and alcohol in the present invention;
[0033] Figure 2 It is a schematic diagram of the catalytic mechanism of the organic zirconium catalyst after chelation of the present invention;
[0034] Figure 3 Schematic diagram of the catalytic mechanism of the organic zirconium catalyst of the present invention;
[0035] Figure 4 This is a comparison chart of the gel time of the polyurethane thermal conductive flame retardant adhesive prepared by adding DBTDL before and after aging;
[0036] Figure 5 This is a comparison chart of the gel time before and after aging of the polyurethane thermal conductive flame retardant adhesive prepared by adding the composite catalyst of Example 1 of the present invention. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Unless otherwise defined, the technical terms or scientific terms used herein should be understood by people with general skills in the field to which the present invention belongs. "Including" and similar words used in this article mean that the elements or objects appearing before the word include the elements or objects listed after the word and their equivalents, without excluding other elements or objects.
[0038] In view of the problems existing in the prior art, an embodiment of the present invention provides a method for preparing a molecular sieve composite catalyst, characterized in that it comprises the following steps:
[0039] S1: mixing the molecular sieve activation powder and the alcohol compound and performing a dehydration reaction to obtain a first composite;
[0040] S2: mixing the first complex with an organic metal catalyst to react to obtain a molecular sieve supported catalyst;
[0041] S3: mixing the molecular sieve supported catalyst with a chelating agent to prepare a molecular sieve composite catalyst;
[0042] The chelating agent is selected from one of benzoyl acetone (PBD for short), dipivaloyl methane (HDPM for short), 2-hydroxyphosphonoacetic acid (HPAA), hydroxyethylidene diphosphonic acid (HEDPA), tetramethyl heptanedione (DPM), heptafluorodimethyl octanedione (FOD), trifluorodimethyl hexanedione (PTA), hexafluoroacetylacetone (HFAC), acetylacetone (ACAC), and hydroxyethylethylenediaminetriacetic acid (HEDTA).
[0043] The beneficial effect of the preparation method of the molecular sieve composite catalyst of the present application is that: the preparation method of the present application uses a chelating six-membered ring chelating agent with strong chelating ability and the ability to form a high thermal stability with the catalyst metal ions or atoms to prepare the molecular sieve composite catalyst, which can make the prepared molecular sieve composite catalyst form a stable chelated state and will not hydrolyze even when distilled in a weakly acidic environment. The attenuation rate of the catalyst is greatly reduced when preparing the polyurethane adhesive, thereby improving the efficiency of preparing the polyurethane adhesive.
[0044] In some embodiments, the metal chelator is selected from one of benzoyl acetone (PBD), dipivaloyl methane (HDPM), 2-hydroxyphosphonoacetic acid (HPAA), hydroxyethylidene diphosphonic acid (HEDPA), tetramethyl heptanedione (DPM), heptafluorodimethyl octanedione (FOD), trifluorodimethyl hexanedione (PTA), hexafluoroacetylacetone (HFAC), acetylacetone (ACAC), and hydroxyethylethylenediaminetriacetic acid (HEDTA).
[0045] In some embodiments, the metal chelator is hexafluoroacetylacetone (HFAC). The molecular formula of HFAC is C5H2F6O2. The fluorine in HFAC has a strong electron-withdrawing effect, which enhances the coordination and chelation with the catalyst metal ions or atoms. At the same time, from the perspective of molecular structure, the six fluorine atoms in the HFAC chelator molecule prevent the lone pair of electrons in the water molecule from attacking the central metal atom of the composite catalyst and causing hydrolysis through steric hindrance.
[0046] In some embodiments, the molecular sieve activation powder is selected from one or both of 3A molecular sieve activation powder and 4A molecular sieve activation powder, and the alcohol compound is selected from one of dipropylene glycol, diethylene glycol, and glycerol.
[0047] In some embodiments, the step of mixing the molecular sieve activation powder and the alcohol compound and then dehydrating them to obtain the first composite comprises mixing the molecular sieve activation powder and the alcohol compound and then dehydrating them for 1 hour at a temperature of 105 to 110° C. and a vacuum degree of -0.05 to -0.1 MPa to obtain the first composite.
[0048] In some embodiments, the mass ratio of the molecular sieve activation powder to the alcohol compound is 1:5-1:15.
[0049] In some embodiments, the temperature of the mixed reaction of the first complex and the organic metal catalyst is controlled to be 60-80°C.
[0050] In some embodiments, the mass ratio of the first complex to the organometallic catalyst is 100:0.5-100:5.
[0051] In some embodiments, in the step of mixing the molecular sieve-supported catalyst with a chelating agent, the mass ratio of the molecular sieve-supported catalyst to the chelating agent is controlled to be 10:1 to 50:1.
[0052] In some embodiments, the metal catalyst is selected from dibutyltin bis(acetylacetonate), zirconium isooctanoate, dibutyltin dilaurate, dibutyltin diacetate, bismuth trioctanoate, stannous octanoate, dibutyltin dichloride, ferric acetylacetonate, aluminum acetylacetonate, bismuth isooctanoate, and zinc isooctanoate.
[0053] The present invention also provides a molecular sieve composite catalyst prepared by the preparation method, wherein the molecular sieve composite catalyst has a general structural formula (I):
[0054] M(CB) d [M(X) e ] f yBOHwL(I)
[0055] wherein M is one of tin, iron, zirconium, bismuth, aluminum, nickel, zinc or cobalt ions;
[0056] (CB) is a carboxylate ion, wherein the carboxylate ion is one of isooctanoate, laurate, acetylacetonate, cyclohexaneate, acetate, and propionate ions;
[0057] (X) is a chelating group, wherein the chelating group is one of β-diketone, enone, alkylphosphine, alcohol, phenol, crown ether, secondary amine, imine, azo or thiol;
[0058] B is an alkali metal ion, wherein the alkali metal ion is one of K and Na ions;
[0059] L is an organic chelating agent, which is one of benzoyl acetone (PBD), dipivaloyl methane (HDPM), 2-hydroxyphosphonoacetic acid (HPAA), hydroxyethylidene diphosphonic acid (HEDPA), tetramethyl heptanedione (DPM), heptafluorodimethyl octanedione (FOD), trifluorodimethyl hexanedione (PTA), hexafluoroacetylacetone (HFAC), acetylacetone (ACAC), and hydroxyethylethylenediaminetriacetic acid (HEDTA);
[0060] d, e, and f are all integers greater than 0, and the values of d, e, and f make the composite catalyst electrically neutral;
[0061] y is greater than or equal to 0.1 and less than or equal to 5;
[0062] w is greater than or equal to 0.0001 and less than or equal to 5;
[0063] The beneficial effects of the molecular sieve composite catalyst of the present invention are: the molecular sieve composite catalyst can form a stable chelated state, does not hydrolyze during distillation in a weakly acidic environment, greatly reduces the decay rate of the catalytic activity of the polyurethane adhesive during storage and use, and improves the stable catalytic performance of the polyurethane adhesive.
[0064] The metal ion M is bonded to the chelate group X, and the metal ion M and the carboxylate ion CB in the organic metal catalyst are bonded. The aforementioned chelate-bonded molecules are stably loaded by the molecular sieve BOH having a large number of mesoporous structures by means of van der Waals forces.
[0065] In some embodiments, the chemical formula of the molecular sieve composite catalyst is preferably Zr(C 32 H 60 O8)[Zr(C5H8O2)4]23KOH(C5H8O2); In some other embodiments, the chemical formula of the molecular sieve composite catalyst is preferably Ni(C 16 H 30 O4)[Ni(C 10 H 14 O4)]32NaOH 2(C5H8O2), more preferably Sn(C 11 H 22 O2)2[Sn(C5H2F6O2)2]2KOH(C5H2F6O2).
[0066] In the present invention, organic chelating agents are understood to be organic compounds having functional groups that act as electron donors and are therefore able to occupy coordination sites on metal central atoms or central ions. Here, compounds suitable as organic complexing agents also exhibit a certain solubility in preferred solvents.
[0067] The present invention also provides an application of a molecular sieve composite catalyst, comprising mixing a combination material A with a combination material B to prepare a polyurethane adhesive, wherein the combination material A comprises a polyol, a chain extender, a flame retardant, an auxiliary catalyst, a thermally conductive powder, and a molecular sieve activation powder, and the molecular sieve composite catalyst is prepared by the preparation method, and the combination material B comprises an isocyanate prepolymer, a flame retardant, a thermally conductive powder, and a water scavenger.
[0068] The beneficial effect of the application of the molecular sieve composite catalyst of the present invention is that the molecular sieve composite catalyst can form a stable chelated state and does not hydrolyze during distillation in a weakly acidic environment. The attenuation rate of the catalyst is greatly reduced when preparing the polyurethane adhesive, thereby improving the efficiency of preparing the polyurethane adhesive.
[0069] In some embodiments, the mass parts of the components of the combination material A are: 100 parts of the polyol, 3-8 parts of the chain extender, 0.05-2 parts of the auxiliary catalyst, 20-60 parts of the thermal conductive powder, 5-15 parts of the molecular sieve activation powder and 0.05-2 parts of the molecular sieve composite catalyst.
[0070] In some embodiments, the weight percentages of the components of the combination material B are: 100 parts of the isocyanate prepolymer, 10-30 parts of the flame retardant, 50-80 parts of the thermal conductive powder and 0.05-1 part of the dehydrating agent.
[0071] In some embodiments, the mass fraction of isocyanate groups (NCO) in the isocyanate prepolymer is 8-20%.
[0072] The preparation steps of the isocyanate prepolymer are:
[0073] (1) Add polyether polyol, inhibitor phosphoric acid, and antioxidant 1010 powder into a reaction kettle equipped with a thermometer, a stirrer, a heating jacket, and a condenser, melt and mix at 105° C. to 110° C., and vacuum dehydrate to a vacuum degree of -0.09 MPa to -0.05 MPa for 1 h to 2 h;
[0074] (2) The material is cooled to 60° C.-80° C., the molar number of hydroxyl group is calculated, and then the material is added according to the molar ratio of isocyanate group to hydroxyl group (i.e., R index) of 2 / 1-10 / 1, stirred evenly, and vacuumed to react at a negative pressure of -0.09 MPa to -0.05 MPa. The reaction time is 60 min-120 min. After determining the reaction endpoint by di-n-butylamine-hydrochloric acid titration method, the isocyanate prepolymer is obtained.
[0075] The isocyanate is one or more of p-phenylene diisocyanate (PPDI), diphenylmethane diisocyanate (MDI), toluene diisocyanate (TDI), hexamethylene diisocyanate (HDI), naphthalene diisocyanate (NDI), 1,4-cyclohexane diisocyanate (CHDI), isophorone diisocyanate (IPDI), carbodiimide modified MDI (CDMDI-100HL), and dicyclohexylmethane diisocyanate (HMDI), preferably a mixture of one or two of isophorone diisocyanate (IPDI) and carbodiimide modified MDI (CDMDI-100HL), and most preferably isophorone diisocyanate (IPDI) and carbodiimide modified MDI (CDMDI-100HL) are mixed in a ratio of 1:1 to form a combined isocyanate (mixISO). In the isocyanate prepolymer of the present invention, the use of two isocyanates may result in a product with better weather resistance than the use of a single isocyanate.
[0076] The polyether polyol used to prepare the isocyanate prepolymer is preferably a polypropylene oxide polyol with a functionality of 2 or 3 and a molecular weight of 500-5000, and the most preferred is a polypropylene oxide polyether polyol with a hydroxyl value of 56 mgKOH / g, a functionality of 3, and a molecular weight of 3000. The polypropylene oxide polyether polyol is purchased from Nanjing Jinpu Jinhu Chemical Co., Ltd., and the product brand is KGF3050A. KGF3050A and a combined isocyanate (mixISO) are prepolymerized according to a molar ratio of isocyanate groups to hydroxyl groups (i.e., R index) of 2 / 1-10 / 1.
[0077] The plasticizer, which is suitable as a plasticizer, is particularly an ester of an organic carboxylic acid, including diisononyl cyclohexane 1,2 dicarboxylate, diisononyl phthalate, diisodecyl phthalate, dioctyl terephthalate, dioctyl adipate, diphenyl phosphate toluene and sebacate. Phthalate, diisononyl cyclohexane 1,2 dicarboxylate or adipate are preferred as plasticizers. Diisodecyl phthalate (DIDP) is most preferred, which has excellent high temperature resistance, migration resistance and aging resistance and can be commercially obtained.
[0078] The coupling agent, in particular, an organic alkoxysilane with a reactive group on the organic group, in particular, aminosilane, epoxysilane, isocyanate silane. Preferred are γ-aminopropyl triethoxysilane (Silquest A-1100), N-β-(aminoethyl)-γ-aminopropyl trimethoxysilane (Silquest A-1120), γ-aminopropyl methyl diethoxysilane (Z-6015), γ-glycidyl ether oxypropyl trimethoxysilane (Silquest A-187), β-(3,4-epoxycyclohexyl) ethyl trimethoxysilane (Silquest A-186), γ-isocyanate propyl trimethoxysilane (Silquest A-Link35), γ-isocyanate propyl trimethoxysilane (Silquest A-Link 25). The most preferred is γ-glycidyloxypropyltrimethoxysilane (Silquest A-187) which contains epoxy groups in the molecule and can effectively improve the adhesion of the polyurethane adhesive to the substrate and is commercially available.
[0079] The polyol used in the composition A is preferably polyoxypropylene polyol, polytetramethylene glycol, castor oil modified polyol, aromatic polyether diol. More preferably, it is aromatic bisphenol A polyether polyol, castor oil modified polyol. Most preferably, castor oil modified polyol URIC H-854 with a hydroxyl value of 210 mgKOH / g, a functionality of 3, excellent hydrolysis resistance and electrical insulation, and is purchased from Ito Oil Manufacturing Co., Ltd.
[0080] The chain extender is particularly aliphatic diols, aromatic diols, alcohol amine diols, carboxyl diols, aromatic diamines, and aliphatic diamines. Preferred are 1,6-hexanediol (HDO), diethylene glycol (DEG), hydroquinone dihydroxyethyl ether (HQEE), trimethylolpropane, triethanolamine, 3,3-dichloro-4,4-diphenylmethanediamine (MOCA), 3,5-dimethylthiotoluenediamine (DMTDA), and isophoronediamine (IPDA). The most preferred is 1,6-hexanediol (HDO) which has a symmetrical molecular structure, is easy to form crystals, and can enhance the water resistance of the polyurethane adhesive.
[0081] The flame retardant is selected from triethyl phosphate (TEP), tri(2-chloro-1-methylethyl) phosphate (TCPP), tri[2-chloro-1-(chloromethyl)ethyl] phosphate (TDCP), tri(p-tert-butylphenyl) phosphate (TBPP) and tri(2-chloroethyl) phosphate (TCEP), melamine polyphosphate, zinc borate, coated red phosphorus flame retardant, coated ammonium polyphosphate flame retardant powder. Preferably, triethyl phosphate (TEP), a high-efficiency liquid flame retardant with a low viscosity, high boiling point and a phosphorus content of 17%, and melamine-formaldehyde coated ammonium polyphosphate (MFAPP) are used, which has extremely low water solubility, can give the polyurethane adhesive excellent precipitation resistance, has strong water resistance, is easy to disperse evenly, and has high thermal stability.
[0082] The auxiliary catalyst is preferably a tertiary amine catalyst, triethylenediamine, N,N-dimethylcyclohexylamine, bis(2-dimethylaminoethyl)ether, tetramethylalkylenediamine, 2,4,6-tris(dimethylaminomethyl)phenol. Among them, triethylenediamine is most preferred because it has a strong catalytic effect on the gel reaction of isocyanate and polyol in polyurethane adhesive.
[0083] The thermal conductive powder mainly includes aluminum nitride (AlN), boron nitride (BN), silicon nitride (Si3N4), aluminum oxide (Al2O3), magnesium oxide (MgO), zinc oxide (ZnO), silicon carbide, boron carbide, aluminum hydroxide (ATH), etc. The preferred homemade thermal conductive powder is a compound of aluminum oxide with a median particle size D50 of 5 microns and aluminum hydroxide with a mass ratio of 10:3 to 10:7. Powders of different particle sizes are compounded to build a thermal conductive network chain to enhance the thermal conductivity of the polyurethane adhesive.
[0084] The dewatering agent mainly includes p-toluenesulfonyl isocyanate and other reactive isocyanates, calcium oxide, triethyl orthoformate, p-toluenesulfonyl isocyanate (Additive TI), 3-ethyl-2-methyl-2-(3-methylbutyl)-1,3-oxazolidine (Zoldine MS-Plus), preferably p-toluenesulfonyl isocyanate (Additive TI) which has high chemical reactivity with water and whose reaction product is soluble in the adhesive and can be purchased commercially.
[0085] The molecular sieve activation powder is a microporous powder obtained by removing water from the structure of crystallized synthetic zeolite (sodium aluminum silicate or potassium aluminum silicate), i.e., activating the zeolite. Preferably, the molecular sieve activation powder is 3A molecular sieve activation powder, 4A molecular sieve activation powder, or 5A molecular sieve activation powder. The most preferred is 3A molecular sieve activation powder with the brand Siliporite SA1720. The molecular sieve has a porous structure and a specific surface area of 300 m 2 / g or more, effectively absorbing trace moisture in polyurethane adhesive, preventing side reactions between water and isocyanate, and ensuring product quality.
[0086] The molecular sieve composite catalyst of the present invention has the following three levels of catalytic effects in the reaction of preparing polyurethane adhesive:
[0087] The first layer of catalytic effect: The molecular sieve activation powder has a large number of mesoporous structures, which is conducive to the long-term stable loading of organic metal catalysts. At the same time, the molecular sieve has a large specific surface area, which can achieve high dispersion of catalytic active components. In addition, the molecular sieve is composed of potassium and sodium alkali metal oxides. The molecular sieve absorbs moisture in the adhesive raw materials and generates Lewis bases such as KOH or NaOH as nucleophilic reagents to polarize the carbonyl group of the isocyanate component, that is, the Lewis base attacks the positive center of the C carbon. The active hydrogen-containing components in the adhesive, such as -OH and -NH2, perform nucleophilic addition on the polarized isocyanate. Figure 1 The schematic diagram of the catalytic mechanism of the base on the reaction of isocyanate and alcohol in the present invention is shown in FIG. Figure 1 , the Lewis base catalytic mechanism of the molecular sieve activated powder after adsorption of water is represented by formulas (a), (b), (c), (d) and (e);
[0088] The second layer of catalytic effect: some metal ions in the organometallic catalyst chelate with a chelating agent selected from hexafluoroacetylacetone (HFAC), benzoyl acetone (PBD), dipivaloyl methane (HDPM), 2-hydroxyphosphonoacetic acid (HPAA), hydroxyethylidene diphosphonic acid (HEDPA), tetramethyl heptanedione (DPM), heptafluorodimethyl octanedione (FOD), trifluorodimethyl hexanedione (PTA), acetylacetone (ACAC), and hydroxyethyl ethylenediamine triacetic acid (HEDTA) to form a coordination structure, which directly activates the catalytic effect. Figure 2 Schematic diagram of the catalytic mechanism of the organic zirconium catalyst of the present invention, referring to Figure 2 , taking the organic zirconium catalyst as an example, the catalytic mechanism after chelation is shown in formula (f);
[0089] The third catalytic effect: the catalysis of the organometallic catalyst itself. Figure 3 Schematic diagram of the catalytic mechanism of dibutyltin dilaurate (DBTDL), see Figure 3 Taking DBTDL catalysis as an example, the catalytic mechanism is shown in formula (g).
[0090] The following examples 1-11 are used to specifically illustrate the preparation method of the molecular sieve composite catalyst of the present invention and the specific implementation methods of its application.
[0091] In Examples 1-5, the implementation method of preparing the molecular sieve composite catalyst according to the present invention is specifically described.
[0092] The preparation method of the molecular sieve composite catalyst of Example 1 is:
[0093] To synthesize a molecular sieve-supported catalyst, 50 grams of 3A molecular sieve activation powder Siliporite SA1720 and 400 grams of diethylene glycol were mixed, poured into a 1-liter openable glass reactor, covered with a reaction cover and sealed, stirred and heated to 105° C., vacuum degree of -0.05 MPa to -0.09 MPa, dehydrated for 1 hour, cooled to 70° C., added 6 grams of an organic metal catalyst dibutyltin dilaurate, stirred and mixed at this temperature at a rotation speed of 500 RPM for 2 hours, and synthesized a molecular sieve-supported catalyst.
[0094] The above molecular sieve supported catalyst and hexafluoroacetylacetone were mixed in the following proportions to obtain the composite catalyst of Example 1:
[0095] Molecular sieve supported catalyst 100 parts by mass
[0096] Hexafluoroacetylacetone chelating agent 5 parts by mass
[0097] The preparation method of the molecular sieve composite catalyst of Example 2 is different from that of Example 1 in that dipropylene glycol is used instead of diethylene glycol, zirconium isooctanoate is used instead of dibutyltin dilaurate, and acetylacetone chelating agent is used instead of hexafluoroacetylacetone chelating agent, the synthesis and mixing processes remain unchanged, and the addition amount of each component remains unchanged.
[0098] The preparation method of the molecular sieve composite catalyst of Example 3 is different from that of Example 1 in that 4A molecular sieve activation powder is used instead of 3A molecular sieve activation powder, dipropylene glycol is used instead of diethylene glycol, dibutyltin diacetate is used instead of dibutyltin dilaurate, and acetylacetone chelating agent is used instead of hexafluoroacetylacetone chelating agent, the synthesis and mixing processes remain unchanged, and the addition amount of each component remains unchanged.
[0099] The preparation method of the molecular sieve composite catalyst of Example 4 is different from that of Example 1 in that 4A molecular sieve activation powder is used instead of 3A molecular sieve activation powder, propylene glycol is used instead of diethylene glycol, dibutyltin di(acetylacetonate) is used instead of dibutyltin dilaurate, and 2-hydroxyphosphonoacetic acid (HPAA, molecular formula: C2H5O6P) chelating agent is used instead of hexafluoroacetylacetone chelating agent, the synthesis and mixing processes remain unchanged, and the addition amount of each component remains unchanged.
[0100] The difference between the preparation method of the molecular sieve composite catalyst of Example 5 and Example 1 is that propylene glycol is used instead of diethylene glycol, bismuth isooctanoate is used instead of dibutyltin dilaurate, and 2-hydroxyphosphonoacetic acid (abbreviated as HPAA, molecular formula: C2H5O6P) is used as a chelating agent instead of hexafluoroacetylacetone chelating agent, the synthesis and mixing processes remain unchanged, and the addition amount of each component remains unchanged.
[0101] Examples 6-10 are specific implementations of preparing polyurethane adhesives using the molecular sieve composite catalysts of Examples 1-5.
[0102] The method for preparing the polyurethane adhesive of Examples 6-10 is as follows: the combination material A and the combination material B containing isocyanate prepolymer (NCO is 8%-20%) are filled into a 400 ml 1:1 two-component adhesive tube. The composition and mass fraction of the combination material A and the combination material B are shown in Table 1. The thermal conductive powder in the combination material A and the combination material B in Examples 6, 9 and 10 is a self-made composite thermal conductive powder, which is prepared by compounding aluminum oxide with a median particle size D50 of 5 microns and aluminum hydroxide of 10 microns, and the mass ratios are 10:3, 10:5 and 10:7 respectively.
[0103] Table 1
[0104]
[0105]
[0106]
[0107] The specific preparation steps of the isocyanate prepolymer in Example 6 are:
[0108] (1) Add 480 g of polyoxypropylene alcohol EP-3600 purchased from Shandong Bluestar Dongda Co., Ltd., 0.08 g of phosphoric acid, and 0.4 g of antioxidant Irganox 1010 (BASF) into a reaction kettle equipped with a thermometer, a stirrer, a heating jacket, and a condenser, melt-mix and stir at 110° C., and vacuum dehydrate to a vacuum degree of -0.09 MPa to -0.05 MPa for 2 h;
[0109] (2) The material was cooled to 75° C., 300 g of isocyanate carbodiimide modified MDI (CDMDI-100HL) was added, CDMDI-100HL was purchased from Wanhua Chemical, and stirred evenly. The vacuum negative pressure reaction was started, and the vacuum degree was -0.09 MPa to -0.05 MPa. The reaction time was 90 min. After the reaction endpoint was determined by di-n-butylamine-hydrochloric acid titration method, the isocyanate prepolymer was obtained. The NCO content was measured by titration to be 9.6%, which was less than 5% of the theoretically calculated NCO content of 9.9%, and the product could be used normally.
[0110] The specific preparation steps of the isocyanate prepolymer in Example 7 are different from those of the isocyanate prepolymer in Example 6 in that isophorone diisocyanate (IPDI) and carbodiimide modified MDI (CDMDI-100HL) are mixed in a 1:1 ratio as a combined isocyanate (referred to as mixISO) to replace carbodiimide modified MDI (CDMDI-100HL), the addition amount and process remain unchanged, and the NCO content measured by titration is 11%, which is less than 5% from the theoretically calculated NCO content of 11.3%, and can be used normally.
[0111] The specific preparation steps of the isocyanate prepolymer in Example 8 are different from those of the isocyanate prepolymer in Example 6 in that 200 g of castor oil-modified polyol URICH-854 is used to replace 480 g of polyoxypropylene alcohol EP-3600, URICH-854 is purchased from Ito Oil Manufacturing Co., Ltd., and isophorone diisocyanate (IPDI) and carbodiimide-modified MDI (CDMDI-100HL) are mixed in a ratio of 1:1 to form a combined isocyanate (mixISO) to replace carbodiimide-modified MDI (CDMDI-100HL). The addition amounts of other raw materials and the process remain unchanged. The NCO content measured by titration is 13%, which is less than 5% from the theoretically calculated NCO content of 13.4%, and can be used normally.
[0112] The specific preparation steps of the isocyanate prepolymer in Example 9 are different from those of the isocyanate prepolymer in Example 6 in that 200 g of castor oil-modified polyol URI C-854 is used to replace 480 g of polyoxypropylene alcohol EP-3600. URI C-854 is purchased from Ito Oil Manufacturing Co., Ltd., and the addition amounts of other raw materials and the process remain unchanged. The NCO content measured by titration is 10.8%, which is less than 5% from the theoretically calculated NCO content of 11.1%, and can be used normally.
[0113] The specific preparation steps of the isocyanate prepolymer in Example 10 are different from those of the isocyanate prepolymer in Example 6 in that 500 grams of polypropylene oxide with a hydroxyl value of 56 mgKOH / g and a functionality of 3 are used to replace 480 grams of polyoxypropylene alcohol EP-3600, EP-3600 is purchased from Shandong Bluestar Dongda Co., Ltd., and polypropylene oxide is purchased from Nanjing Jinpu Jinhu Chemical Co., Ltd., product brand: KGF3050A, and isophorone diisocyanate (IPDI) and carbodiimide modified MDI (CDMDI-100HL) are mixed in a 1:1 ratio to form a combined isocyanate (mixISO) to replace carbodiimide modified MDI (CDMDI-100HL), the addition amount and process of other raw materials remain unchanged, and the NCO content measured by titration is 10.2%, which is less than 5% from the theoretically calculated NCO content of 10.7%, and can be used normally.
[0114] Embodiment 11
[0115] The gel curves of the polyurethane thermal conductive flame retardant adhesive prepared by the molecular sieve composite catalyst and the general organic tin catalyst in Example 1 were compared by using a rheometer DHR. After accelerated aging at 50°C for 20 days, the comparative test results are shown in Table 2.
[0116] Table 2
[0117]
[0118] Figure 4 This is a comparison chart of the gel time of the polyurethane thermal conductive flame retardant adhesive prepared by adding DBTDL before and after aging. Figure 5 This is a comparison chart of the gel time of the polyurethane thermal conductive flame retardant adhesive prepared by adding the composite catalyst of Example 1 of the present invention before and after aging. Figure 4 , Figure 5 As shown in Table 2, when the general dibutyltin dilaurate (DBTDL) catalyst is added to prepare the polyurethane thermal conductive flame retardant adhesive, the attenuation percentage of the catalytic efficiency of the catalyst is 283.8%, while when the molecular sieve composite catalyst of the present invention is added to prepare the polyurethane thermal conductive flame retardant adhesive, the attenuation percentage of the catalytic efficiency of the molecular sieve composite catalyst is only 4.7%. The molecular sieve composite catalyst of the present invention has a greatly reduced failure rate when preparing the polyurethane thermal conductive flame retardant adhesive relative to the existing DBTDL catalyst, and can improve the efficiency of preparing the polyurethane thermal conductive flame retardant adhesive.
[0119] Although the embodiments of the present invention are described in detail above, it is obvious to those skilled in the art that various modifications and variations can be made to these embodiments. However, it should be understood that such modifications and variations are within the scope and spirit of the present invention as described in the claims. Moreover, the present invention described herein may have other embodiments and may be implemented or realized in a variety of ways.
Claims
1. A method for preparing a molecular sieve composite catalyst, characterized in that: The following steps are involved: S1: mixing the molecular sieve activation powder and the alcohol compound and performing a dehydration reaction to obtain a first composite, wherein the mass ratio of the molecular sieve activation powder to the alcohol compound is controlled to be 1:5-1:15; S2: mixing the first complex with an organic metal catalyst to react, to obtain a molecular sieve supported catalyst, wherein the mass ratio of the first complex to the organic metal catalyst is controlled to be 100:0.5 to 100:5; S3: mixing the molecular sieve supported catalyst with a chelating agent to prepare a molecular sieve composite catalyst, wherein the mass ratio of the molecular sieve supported catalyst to the chelating agent is controlled to be 10:1 to 50:1; Wherein, the chelating agent is selected from one of benzoyl acetone, dipivaloyl methane, 2-hydroxyphosphonoacetic acid, hydroxyethylidene diphosphonic acid, tetramethyl heptanedione, heptafluorodimethyl octanedione, trifluorodimethyl hexanedione, hexafluoroacetylacetone, acetylacetone, and hydroxyethylethylenediaminetriacetic acid.
2. The preparation method according to claim 1, characterized in that: The molecular sieve activation powder is selected from one or both of 3A molecular sieve activation powder and 4A molecular sieve activation powder, and the alcohol compound is selected from one of dipropylene glycol, diethylene glycol and glycerol.
3. The preparation method according to claim 1, characterized in that: The step of mixing the molecular sieve activation powder and the alcohol compound and then performing a dehydration reaction to obtain the first composite comprises: mixing the molecular sieve activation powder and the alcohol compound and then performing a dehydration reaction for 1 hour at a temperature of 105-110° C. and a vacuum degree of -0.05-0.1 MPa to obtain the first composite.
4. The preparation method according to claim 1, characterized in that: The temperature of the mixed reaction of the first complex and the organic metal catalyst is controlled to be 60° C. to 80° C.
5. The preparation method according to claim 1, characterized in that: The organic metal catalyst is selected from dibutyltin bis(acetylacetonate), zirconium isooctanoate, dibutyltin dilaurate, dibutyltin diacetate, bismuth trioctanoate, stannous octanoate, dibutyltin dichloride, ferric acetylacetonate, aluminum acetylacetonate, bismuth isooctanoate, and zinc isooctanoate.
6. A molecular sieve composite catalyst prepared by the preparation method according to claim 1, characterized in that: The molecular sieve composite catalyst has a general structural formula (I): M(CB) d [M(X) e ] f yBOHwL(I) wherein M is one of tin, iron, zirconium, bismuth, aluminum, nickel, zinc or cobalt ions; (CB) is a carboxylate ion, wherein the carboxylate ion is one of isooctanoate, laurate, acetylacetonate, cyclohexaneate, acetate, and propionate ions; (X) is a chelating group, wherein the chelating group is one of β-diketone, enone, alkylphosphine, alcohol, phenol, crown ether, secondary amine, imine, azo or thiol; B is an alkali metal ion, wherein the alkali metal ion is one of K and Na ions; L is an organic chelating agent, which is one of benzoyl acetone, dipivaloyl methane, 2-hydroxyphosphonoacetic acid, hydroxyethylidene diphosphonic acid, tetramethyl heptanedione, heptafluorodimethyl octanedione, trifluorodimethyl hexanedione, hexafluoroacetylacetone, acetylacetone or hydroxyethylethylenediaminetriacetic acid; d, e, and f are all integers greater than 0, and the values of d, e, and f make the composite catalyst electrically neutral; y is greater than or equal to 0.1 and less than or equal to 5; w is greater than or equal to 0.0001 and less than or equal to 5.
7. An application of a molecular sieve composite catalyst, characterized in that: The invention comprises mixing a composite material A with a composite material B to prepare a polyurethane adhesive, wherein the composite material A comprises a polyol, a chain extender, a flame retardant, an auxiliary catalyst, a coupling agent, a thermal conductive powder, a molecular sieve activation powder and a molecular sieve composite catalyst prepared by the preparation method according to any one of claims 1 to 5, and the composite material B comprises an isocyanate prepolymer, a plasticizer, a thermal conductive powder and a water scavenger.
8. The use of the molecular sieve composite catalyst according to claim 7, characterized in that: The mass parts of the components of the combination material A are: 20-50 parts of the polyol, 0.5-8 parts of the chain extender, 5-18 parts of the flame retardant, 0.5-5 parts of the coupling agent, 0.05-2 parts of the molecular sieve composite catalyst, 0.05-1 parts of the auxiliary catalyst, 30-65 parts of the thermal conductive powder and 1-5 parts of the molecular sieve activation powder.
9. The use of the molecular sieve composite catalyst according to claim 7, characterized in that: The weight proportions of the components of the combination material B are: 35-60 parts of the isocyanate prepolymer, 5-20 parts of the plasticizer, 25-55 parts of the thermal conductive powder and 0.1-2 parts of the dehydrating agent.
10. The use of the molecular sieve composite catalyst according to claim 7, characterized in that: The mass fraction of isocyanate groups in the isocyanate prepolymer is 8% to 20%.
Citation Information
Patent Citations
Method and apparatus for producing an image of a scene, particularly a thermal image with compensation of the phase error
EP0003600A1
Transparent thermoplastic polyurethane elastomer and preparation method thereof
CN119161555A
Improvements in catalysts
GB927004A
Structural polyurethane adhesive having a low glass transition temperature
US20150203728A1